Poor understanding of the hydrogeological structure is a main cause of hand-dug wells failure in developing countries: A case study of a Precambrian basement aquifer in Bugesera region (Burundi). (September 2016) - Bakundukize, Charles; Mtoni, Yohana; Martens, Kristine; Van Camp, Marc; Walraevens, Kristine
Abstract: This study investigates a Precambrian basement aquifer in Bugesera region, a typical African rural area in northeastern Burundi. Domestic water supply relies on groundwater which is tapped through hand-dug wells. Despite several attempts to increase the number of water points in the area, the water demand is still far from being met as a result of the high rate of well failure. This paper seeks to understand whether the hydrogeological structure and the spatial distribution of hydraulic parameters can explain the low productivity and the high failure rate of hand-dug wells. The hydrogeological structure inferred from the interpretation of a large number of vertical electrical soundings (VES) reveals a typical sequence of geoelectrical layers, which is characterized by an overall upwards fining from the fresh basement, over the fractured/weathered basement, to the overburden or saprolite with a clay-rich layer on top. Whereas the overall aquifer potential mainly depends on the thickness of the weathered overburden, the aquifer potential for shallow hand-dug wells is determined by the hydraulic conductivity of the upper few meters of the saturated zone. This upper zone was investigated in the pumping tests. The spatial distribution of the specific capacity reveals a wide variation of hydraulic parameters, depending on the well's position in the depth profile of the aquifer's hydraulic conductivity. The thickness of the potential aquifer is highest in the central part of the study area (pegmatitic and granitic intrusions) which has the highest overall aquifer potential compared to the surrounding metasedimentary formations. However, a thick weathered overburden will increase the groundwater potential of an aquifer for deep boreholes, whereas for hand-dug wells, the productivity can only be high if the thickness of the weathered overburden is small enough, or the water table is deep enough, to allow to tap the coarse part at the base of the overburden and/or part of the weathered/fractured basement. This study reveals that the main cause of low productivity and failure of many hand-dug wells in Bugesera region is not to be linked to poor groundwater resource potential but rather stems from the inappropriate random siting of wells and from poor well construction expertise which does not take into account the hydrogeological conditions. The results of the investigation indicate that in the typical weathering profile of the Precambrian basement in Sub-saharan Africa, the coarse lower part of the weathered overburden and the fractured/weathered basement offer good prospects for water resource. Depending on the depth at which this layer is encountered, either shallow hand-dug wells or deep drilled wells are most appropriate. Highlights: VES reveal the hydrogeological structure of Precambrian basement rocks. Fresh basement, fractured/weathered basement and weathered overburden on top. Aquifer potential for hand-dug wells depends on upper few meters of saturated zone. Favourable: 1) thin weathered cover; 2) thick weathered cover with deep water table. Unfavourable: thick weathered cover with shallow water table.